Adventures in Management : A Saga of Managing in a Developing Country - Abeywickrama, Kenneth (Response Books, 2007)
Adventures in Management is an insider's view of corporate management in developing countries. Highlighting the key differences between the developing and developed countries in terms of issues of politics, corruption, and cultural attitudes, the author explains how to perform successfully despite them.